Prevalence, Awareness, and Associated Factors of Text Neck Syndrome: An Observational Study - Ali, Tania; Masooma , Masooma; Rani, Aqsa; Sajjad, Naheed; Sheikh, Rozeena; Channa, Farah Naz; Irfan, Shazia; Rehmat, Zainia; BiBi, Tahira; Panezai, Wafa (Journal of Neonatal Surgery, 2025)
Neck pain is a common musculoskeletal disorder, with a global prevalence ranging from 16.7% to 75.1%. It can cause discomfort in the upper extremities and lead to long-term complications. Text Neck Syndrome (TNS), often associated with prolonged mobile phone use and poor posture, is increasingly recognized as a contributing factor. This study aimed to assess awareness of TNS, determine its prevalence in a random population, and explore associations between TNS and factors such as posture, neck flexion angle, and duration of phone usage. An observational study was conducted among 300 participants using both paper-based and online questionnaires (Google Forms). Statistical analysis was performed using SPSS version 23.0, with Chi-square tests applied to examine associations between key variables. Among the participants, 42.3% were aware of TNS. Significant associations were observed between neck pain and body posture (χ² = 23.454, p < 0.05), neck pain and duration of mobile phone usage (χ² = 13.517, p < 0.05), headache and phone usage duration (χ² = 31.110, p < 0.05), and shoulder pain and phone usage duration (χ² = 31.110, p < 0.05).Poor posture and prolonged mobile phone use are significantly associated with TNS-related symptoms, including neck pain, headache, and shoulder pain. These findings highlight the need for awareness programs and ergonomic interventions to reduce the risk of TNS. Future studies with larger sample sizes are recommended to provide more robust prevalence estimates and a deeper understanding of symptom patterns